The Influence of School Literacy Movement (GLS) and School Library Facilities on the Reading Interest of Fifth Grade Students at SD Negeri Sukarami, Palembang City - Apriani, Zuliana; Houtman, Houtman; Prakoso, Teguh (FKIP - Universitas Riau, 2025)
This study investigates the influence of the School Literacy Movement (Gerakan Literasi Sekolah/GLS) and school library facilities on the reading interest of fifth-grade students in public elementary schools in Sukarami District, Palembang City. Employing a quantitative approach with a survey method, data were collected from 347 students selected through proportional random sampling out of a population of 2,658 students. The research design involved multiple linear regression analysis complemented by t-tests and F-tests to examine both partial and simultaneous effects. Findings demonstrate that GLS significantly enhances students’ reading interest by fostering consistent reading habits and cultivating a literacy-friendly environment. School library facilities, including the availability of relevant collections, comfortable spaces, and active literacy services, were also found to exert a positive effect, although their influence was less dominant compared to GLS. Simultaneously, both factors interact to strengthen literacy culture in schools. These results highlight the necessity of integrating structured literacy programs with the development of supportive library infrastructures to achieve sustainable improvements in elementary students’ reading engagement.